2019
DOI: 10.3390/ijms20061347
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Platelet Concentrates in Treatment of Furcation Defects—A Systematic Review and Meta-Analysis

Abstract: Background: The aim of this review was to evaluate the adjunctive effect of autologous platelet concentrates (APCs) for the treatment of furcation defects, in terms of scientific quality of the clinical trials and regeneration parameters assessment. Methods: A systematic search was carried out in the electronic databases MEDLINE, SCOPUS, CENTRAL (Cochrane Central Register of Controlled Trials), and EMBASE, together with hand searching of relevant journals. Two independent reviewers screened the articles yielde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 41 publications
5
33
0
1
Order By: Relevance
“…However, scientific data regarding the potential benefits of using APCs in regenerative therapies remains inconsistent. Some studies stated that both PRP and PRF positively affect only early healing of hard and soft tissues, with and without significant beneficial effect on final therapeutic outcomes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. It was also reported that the use of platelet concentrates may positively affect postoperative inflammation and pain reduction [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, scientific data regarding the potential benefits of using APCs in regenerative therapies remains inconsistent. Some studies stated that both PRP and PRF positively affect only early healing of hard and soft tissues, with and without significant beneficial effect on final therapeutic outcomes [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. It was also reported that the use of platelet concentrates may positively affect postoperative inflammation and pain reduction [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, interest in the use of platelet concentrates (PCs) for the treatment of many intraoral clinical conditions, including periodontal and furcation defects, is rising [ 15 ]. The rationale behind the preparation of platelet concentrates is that concentrated platelets and autologous growth factors could be collected from a whole blood sample through centrifugation and used in a surgical site to promote local healing [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, a significant improvement in GT, CAL and RD was found when treated with CAF + L-PRF. This result can be attributed to the additive regenerative potential of L-PRF [ 39 , 40 ]. L-PRF has a positive influence on cell proliferation, migration, adhesion, differentiation and inflammation, which proves its therapeutic potential in regenerative approaches [ 41 ].…”
Section: Discussionmentioning
confidence: 99%